Exploring the Role of ChatGPT in Shaping an Innovative Organizational Culture, Responsiveness to Change, and Enhancing Human Resource Development - Gadzali, Silvy Sondari (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
The rapid development of digital technology has prompted organizations to adopt new tools and systems to enhance operational efficiency and effectiveness. One of the latest technologies garnering widespread attention is artificial intelligence (AI), including language models like ChatGPT, capable of processing and generating text naturally. This research aims to further explore how ChatGPT can be implemented within organizations to cultivate an innovative culture, responsiveness to change, and effectively support human resource development. This study employs a literature review method with a qualitative approach. Data were collected from articles published on Google Scholar between 2021 and 2024, considering Google Scholar as a comprehensive and credible academic database. The findings indicate that ChatGPT plays a crucial role in fostering innovation by serving as a catalyst for creative ideas and new solutions. Furthermore, ChatGPT has proven to enhance organizational responsiveness to changes in the business environment by providing accurate insights based on real-time data. On the other hand, utilizing ChatGPT as an interactive training tool also aids in accelerating employee competency development. However, it is essential to consider the ethical challenges and considerations in the use of this technology, including data privacy issues and overreliance.